THE EFFECT OF FOLIAR FERTILIZING ON THE PLUM YIELD AND THE CHEMICAL COMPOSITION OF PLUM LEAVES - Marina T. Stojanova; Dragutin Đukić; Monika Stojanova (TOKYO 7TH INTERNATIONAL INNOVATIVE STUDIES & CONTEMPORARY SCIENTIFIC RESEARCH CONGRESS, 2023)
The effect of foliar fertilizing on the yield and the chemical composition of leaves from Stanley plum cultivar was determined. The variants were: Control (untreated); NPK+Ever green со Me (55% organic matter, 2% w/w Mg, 2% w/w Fe, 2% w/w Zn, 2% w/w Mn, 0.5 % w/w Cu, 0.5% w/w B); NPK+Biolinfa (34% organic matter 3% N, 5.80% K2O) and NPK+Oligomix (1.20% B, 0.10% Cu, 4% Fe, 1.50% Mn, 0.10% Mo, 2% Zn). The distance of fruit planting was 5 m row by row and 4 m in the rows. In each variant and repetition 20 plants were included, and total in all experiment 240 plants were involved. Three foliar treatments were applied with given above fertilizers at a concentration of 0.4%. At the end of November, soil fertilizing with the fertilizer Polyfeed NPK 11-44-11 (450 kg∙ha-1) was done. Soil agrochemical analyses were made, and was concluded good fertility with nitrogen, but medium fertility with phosphorus and potassium. The foliar fertilizing has a positive influence on the yield and the chemical composition of plum leaves. The highest (p<0.05) average plum fruit yield (18,255 kg∙ha-1) was determined in the variant treated with fertilizer NPK+Ever green with Me (55% organic matter, 2%w/w Mg, 2%w/w Fe, 2%w/w Zn, 2% w/w Mn, 0.5 %w/w Cu, 0.5 %w/w B). The lowest plum fruits yield (17,970 kg∙ha-1) was determined in the control variant. The highest average content of nitrogen (3.10%), phosphorus (0.35%) and potassium (2.15%) was determined in the variant NPK+Ever green со Me (55% organic matter, 2% w/w Mg, 2% w/w Fe, 2% w/w Zn, 2% w/w Mn, 0.5 % w/w Cu, 0.5% w/w B). The highest average content of calcium (2.12%) and magnesium (0.51%) were determined in the leaves from variant NPK+Oligomix (1.20% B, 0.10% Cu, 4% Fe, 1.50% Mn, 0.10% Mo, 2% Zn).
Keywords: plum; foliar fertilizing; soil fertility